Sustainable Housing, from a Theoretical and Public Policy Approach in Colombia (2018)
Social housing in Colombia does not include, as design parameters, environmental  or social criteria, since financial closure is a priority. This is why the objective of this article is to propose guidelines for the design of prototypes of sustainable social housing (VIS), based on the application of the baseline matrix. With respect to the methodology used, this research is based on the matrix elaborated in the research project called Proposal for Guidelines for the Architectural Design and Construction of a VIS Prototype for Medellín, which includes sustainability criteria in its design based on the baseline elaborated in phase II and applicable to Medellín and the Metropolitan Area. This matrix is composed of four thematic axes: site selection, rational use of water, materials and habitability. Once applied, the results served to define guidelines for intervention at the different scales. The project resulted in intervention guidelines that can be applied in the design stage of this type of project or that can be used as a reference point to evaluate sustainability in VIS projects developed.